Increased serum levels of interleukin-6 and von Willenbrand Factor in early phase of acute coronary syndrome in a young and multiethnic Malaysian population - Wen, Ni Tiong; Yean, Alan Yip Fong; Sim, Edmund U. H.; Hiang, Chuan Chan; Tiong, Kiam Ong; Boon, Cheng Chang; Kui, Hian Sim (BMJ Publishing Group, 2012)
Objective Interleukin-6 (IL6; proinflammatory marker), von Willebrand Factor (vWF; endothelial dysfunction marker) and P-selectin ( platelet activation marker), may play important roles in defining the pathogenesis of vulnerable plaques in acute coronary syndrome (ACS). This study aims to investigate the expression and relationship of these markers in early phases of ACS in a young and multiethnic Malaysian population. Design Peripheral whole blood mRNA, and serum levels of IL6, vWF and P-selectin were measured in 22 patients with ACS, and in 28 controls with angiographically significant coronary artery disease without previous ACS events. Venous blood from ACS patients was obtained within 1 h of hospital admission. Results No significant differences of IL6, vWF and P-selectin mRNA levels between ACS and controls were seen. ACS patients had significantly higher serum levels of IL6 and vWF ( p<0.001), compared with controls. P-selectin correlated with IL6 (r=0.697, p=0.003) and vWF (r=0.497, p=0.05) at mRNA levels, indicating a possible association between these three indices of ACS pathogenesis. Conclusions Increased serum levels of IL6 and vWF suggest that inflammation and endothelial dysfunction may play a prominent role in the pathogenesis of the disease during the early phase of ACS.